Penyapihan Dini, Toilet Training dan Pola Asuh serta Pengaruhnya pada Temper Tantrum - Qurniyawati, Eny; Ratnawati, Riska (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Child development includes physical, psychological and social aspects. The imbalance stimulation provided by parents could develop temper tantrum of child as a form of emotional explosion. The influence factors of tantrum among children are early weaning, improper toilet training, and the way of parenting in tantrum. This study aims to examine factors influence on temper tantrum among pre-school children. Method: This is descriptive analytical study with case control design. The number of case sample which selected from mothers who have tantrum pre-school child was 42 mothers and 42 control sample were also selected from mothers who have no tantrum child. Data were analyzed by univariate, bivariate (Chi-Square) and multivariate using logistic regression to examine the most influenced factors.Results: The study shows that early weaning, toilet training and parenting method were significantly influence on temper tantrum of pre-school children. The most influential variable was the parenting method with OR 9,09 and p-value 0,021. It means negative parenting method 9 times higher influence on tantrum temper behavior among children compared to positive parenting method. It is suggested that parenting method should emphasize more in educative and discipline including responsibility aspects.